Management of Stress for Right Attitude and Good Governance - Kumar, Raj; Chandel, Kulbhushan (Gyan Management Journal, 2010)
Stress is a natural and universal phenomenon right from the origin of species on this unique planet. In the primitive and agrarian society the intensity, duration, complexity and predictability of stress have been less as compared to modern urban, industrial and global society. Stress is associated with internal reactions. Therefore it is a slippery concept. Stress is an arousal both mental and physical which occurs when individual is unable to respond to challenging and threatening environmental demand. A sample of 150 respondents and 50 yoga experts has been taken for the study purpose. It is concluded that stress has physiological, emotional, behavioral and cognitive consequences on individuals, which in turn affect the performance, efficiency and productivity and immune system of everyone in all organization and at all levels. Stressed person cannot exploit his full potential; therefore, the management of stress is a need of the hour. Yoga is a scientific, holistic and effective therapy for managing stress, cultivating right attitude which will lead to good governance.
Keywords: Yoga; Stress Management